2018
DOI: 10.7759/cureus.2172
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Nerve Foramina Part I: A Review of the Anatomy and Pathology of Cranial Nerve Foramina of the Anterior and Middle Fossa

Abstract: Cranial nerve foramina are integral exits from the confines of the skull. Despite their significance in cranial nerve pathologies, there has been no comprehensive anatomical review of these structures. Owing to the extensive nature of this topic, Part I of our review, presented here, focuses on the foramina of the anterior and middle cranial fossae, discussing each foramen’s shape, orientation, size, surrounding structures, and structures that traverse them. Furthermore, by comparing the size of each foramen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 36 publications
1
16
0
1
Order By: Relevance
“…Hereby, it is suggested that besides active migration promoting the cell distribution within the brain, a complex of tools such as bulk flow, vessel pulsation when the cells move along perivascular spaces, as well as nose-to-brain interconnection of lymphatic and cerebrospinal fluid systems contribute to their rapid entry into the brain and further distribution to different brain areas [ 43 , 44 ]. Moreover, the comparison of the cribriform plate's anatomy in humans and rodents, which is the first rigid mechanical barrier for cells on the way from the nasal epithelium to the brain [47] , [48] , [49] , allow us to suggest that the larger area and size of the cribriform plate foramina in humans would facilitate the migration of cells through these narrow openings when compared to that of rodents. Another issue that may impact transnasal delivery of cells to the brain is their long persistence, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Hereby, it is suggested that besides active migration promoting the cell distribution within the brain, a complex of tools such as bulk flow, vessel pulsation when the cells move along perivascular spaces, as well as nose-to-brain interconnection of lymphatic and cerebrospinal fluid systems contribute to their rapid entry into the brain and further distribution to different brain areas [ 43 , 44 ]. Moreover, the comparison of the cribriform plate's anatomy in humans and rodents, which is the first rigid mechanical barrier for cells on the way from the nasal epithelium to the brain [47] , [48] , [49] , allow us to suggest that the larger area and size of the cribriform plate foramina in humans would facilitate the migration of cells through these narrow openings when compared to that of rodents. Another issue that may impact transnasal delivery of cells to the brain is their long persistence, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The FO is surgically important as access to Meckel's cave during the procedures. The trigeminal ganglion lies within Meckel's cave, superior to the FO . The FO is situated in the posterior aspect of the greater sphenoid wing and anteromedial to the sphenoid spine.…”
Section: Discussionmentioning
confidence: 99%
“…The FO is situated in the posterior aspect of the greater sphenoid wing and anteromedial to the sphenoid spine. The FO has variations in size, shape, and orientation . Medial to the FO, but lateral to the sella turcica, lies the cavernous sinus.…”
Section: Discussionmentioning
confidence: 99%
“…Three statistical studies [19][20][21] showed that the petrous part of the temporal bone is frequently impacted by cranial trauma. Six normative studies (Ref [23][24][25][26][27][28][29]) showed that there are some standard values about the size of the skull base foramens. Two studies [26,30] were using a process that can be utilised to explain some PCSs.…”
Section: Study Characteristicsmentioning
confidence: 99%